Study of Morphology of Film Reduced Graphene Oxide from Coconut Shell - Mas’udah, Kusuma Wardhani; Astuti, Fahmi; Darminto, Darminto (IPTEK Journal of Proceedings Series, 2015)
Coconut shell as the main ingredient in this study were converted into charcoal. The resulted sample coconut shell charcoal was used as a powder and heated. After heating, the powder was dissolved into distilled water. They were coated on the glass substrates using a spin-coating method. Furthermore, this study characterizations using Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX) were conducted for all samples. r-GO layer coconut shell has been successfully made on glass substrates, is shown with layers that have accumulated weight percentage of carbon atoms in each sample layer, that is equal to 84.55% and 20.61%.